2010
DOI: 10.1111/j.2042-3306.2010.00114.x
|View full text |Cite
|
Sign up to set email alerts
|

The 3D anatomy of the cervical articular process joints in the horse and their topographical relationship to the spinal cord

Abstract: This study confirms that the APJ extend into the dorsolateral aspect of the vertebral canal in a ventromedial direction, suggesting that oblique myelographic views are recommended for the diagnosis of spinal cord compression when pathology of the APJ is suspected.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
51
1
4

Year Published

2012
2012
2022
2022

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(58 citation statements)
references
References 18 publications
1
51
1
4
Order By: Relevance
“…CT has been established as one of the most useful procedures for the assessment of human spine and for the diagnosis of human lumbosacral diseases (Dorwart 1984;Dorwart and LaMasters 1985) 脕 However, a few instances on the application of either CT or 3D reconstruction to any region of the spine of terrestrial mammals are available (Feeney et al 1991;Jones et al 1995;Claridge et al 2010) and most of these have been performed in dead animals such as those describing the normal canine spinal anatomy by cadaver comparison to tomographic images (Feeney et al 1991;Jones et al 1995) or more recently studies by 3D anatomy of the equine cervical articular process joints in relation to the spinal cord. By contrast, we have attempted to describe our observations on recognisable structures in alive and neonatal animals, but further studies are necessary to define the ultimate limits of 3D CT reconstruction both for basic morphologic imaging and for interpretation of patient images with clinical signs.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…CT has been established as one of the most useful procedures for the assessment of human spine and for the diagnosis of human lumbosacral diseases (Dorwart 1984;Dorwart and LaMasters 1985) 脕 However, a few instances on the application of either CT or 3D reconstruction to any region of the spine of terrestrial mammals are available (Feeney et al 1991;Jones et al 1995;Claridge et al 2010) and most of these have been performed in dead animals such as those describing the normal canine spinal anatomy by cadaver comparison to tomographic images (Feeney et al 1991;Jones et al 1995) or more recently studies by 3D anatomy of the equine cervical articular process joints in relation to the spinal cord. By contrast, we have attempted to describe our observations on recognisable structures in alive and neonatal animals, but further studies are necessary to define the ultimate limits of 3D CT reconstruction both for basic morphologic imaging and for interpretation of patient images with clinical signs.…”
Section: Discussionmentioning
confidence: 99%
“…The CT scanners used in veterinary medicine are designed to use in human patients; therefore, this type of machines is only suitable for foals due to size constraints of the CT gantry and scanning table. Due to all these limitations most of the studies on the horse are focused on technical procedures (Barbee et al 1987), head diseases (Ragle et al 1988;Allen et al 1988;Vink-Nooteboom et al 1998), distal extremities (Peterson and Bowman 1988;Ruohoniemi et al 1997) or with 3D anatomy of the cervical articular process joints (Claridge et al 2010).…”
Section: Introductionmentioning
confidence: 99%
“…El diagn贸stico preciso requiere de un cuidadoso examen cl铆nico, la exclusi贸n de otras causas de claudicaci贸n o pobre rendimiento, y la interpretaci贸n precisa de los resultados de diagn贸stico por im谩genes (Dyson, 2011). La anatom铆a detallada de las articulaciones cervicales y de procesos articulares, ha recibido poca atenci贸n en la literatura, sin embargo estos trastornos se han relacionado con la compresi贸n de la m茅dula espinal que resulta en signos cl铆nicos graves, como la ataxia y la debilidad (Claridge et al, 2010). En un reciente estudio por imagen las anomal铆as m谩s representativas encontradas en las radiograf铆as fueron la subluxaci贸n dorsal oinestabilidad vertebral, la osteoartritis de los procesos articulares y las fracturas vertebrales de distinta naturaleza (Diez et al).…”
Section: Planos Anat贸micos Ventralesunclassified
“…The present study focused on an assessment of cartilage and bone lesions observed by MRI in the articular processes of CSM horses compared with controls, given that changes in their shape, size, and spatial orientation frequently contribute to spinal cord compression. 6,14 A subset of representative lesions was then further characterized with micro-computed tomography (micro-CT) and routine histopathology. The hypothesis was that bone and cartilage lesions of the cervical vertebral articular processes occur with an increased frequency and severity in CSM horses compared with controls.…”
mentioning
confidence: 99%